Shadow weaver - Connolly, MarcyKate (Sourcebooks Jabberwocky, 2018)
Twelve-year-old Emmeline possesses the unique ability to manipulate shadows. When her magical powers are threatened by a noble family, she desperately turns to Dar, her shadow friend, who offers to save her if Emmeline makes Dar flesh again, but this bargain only puts Emmeline's life in further jeopardy.